Biochemical characterization of a novel deubiquitinating enzyme otubain 1 and investigation into its role in Yersinia infection - Edelmann, M; Mariola J. Edelmann (2010)
Deubiquitinating enzymes (DUBs) constitute a diverse protein family. The specificities and functions of the majority of DUBs are unknown, although their impact on many biological and pathological processes is widely appreciated. This dissertation entails a detailed characterization of otubain 1 (OTUB1), an ovarian tumor domain-containing DUB. The presented work describes OTUB1’s specificity, localization, protein interactions, importance in infection with Yersinia, and proposes a novel model of regulation of its enzymatic activity. I first discuss the structural and biochemical properties of OTUB1, demonstrating its selectivity towards ubiquitin and NEDD8. Moreover, I show that OTUB1 cleaves lys48- but not lys63-linked polyubiquitin, emphasizing its role in ubiquitin-mediated proteasomal degradation. Mass spectrometric identification of interaction partners and localization studies suggest possible involvement of OTUB1 in RNA processing and cell morphology. Furthermore, I demonstrate that invasion of the host cells by the enterobacteria Yersinia can be altered by changing OTUB1 expression. This effect is dependent on the catalytic activity of OTUB1 and its ability to stabilize RhoA-GTP prior to infection. YpkA and OTUB1 modulate RhoA-GTP stability in opposing ways, leading to cytoskeletal rearrangements that may be involved in bacterial invasion. Moreover, OTUB1 is post-translationally modified by phosphorylation that modulates its ability to stabilize RhoA-GTP and counteracts its effect on bacterial invasion. These findings provide a novel entry point for the manipulation of the host—pathogen interactions. Lastly, a kinase screen revealed that FER, an oncogenic kinase with a role in cell morphology, phosphorylates OTUB1, as demonstrated by overexpression, siRNA and in vitro studies. The phosphorylated site was mapped to tyr26 and the activity-based labeling revealed that this modification interferes with the deubiquitinating activity of OTUB1. In summary, the results presented in this thesis confirm that OTUB1 exerts properties of a “classical DUB” and uncover some of its physiological functions.